Cattle as natural host for Schistosoma haematobium (Bilharz, 1852) Weinland, 1858 x Schistosoma bovis Sonsino, 1876 interactions, with new cercarial emergence and genetic patterns - IBIKOUNLE, MOUDACHIROU (My University, 2020)
Schistosomiasis remains a parasitic infection which poses serious public health consequences around the world, particularly on the African continent where cases of introgression/hybridization between human and cattle schistosomiasis are being discovered on a more frequent basis in humans, specifically between Schistosoma haematobium and S. bovis. The aim of this paper is to analyze the occurrence of S. bovis in cattle and its relationship with S. haematobium in an area where cattle and humans share the same site in Benin (West Africa). We used the chronobiology of cercarial emergence as an ecological parameter and both molecular biology (COI mtDNA and ITS rDNA) ofthe larvaeand morphology ofthe eggsastaxonomic parameters. The results showed a chronobiological polymorphism in the cercarial emergence rhythm. They showed for the first time the presence of S. bovis in Benin, the presence of introgressive hybridization between S. bovis and S. haematobium in domestic cattle, and the presence of atypical chronobiological patterns in schistosomes from cattle, with typical S. haematobium shedding pattern, double-peak patterns, and nocturnal patterns. Our results showed that the chronobiological life-history trait is useful for the detection of new hosts and also may reveal the possible presence of introgressivehybridization in schistosomes. Our results, for the first time, place cattle as reservoir host for S. haematobium and S. bovis x S. haematobium. The consequences of these results on the epidemiology of the disease, the transmission to humans, and the control of the disease are very important.
Keywords: Schistosoma bovis . Schistosoma haematobium . Introgressive hybridization . Cercarial emergence pattern . Cattle .; Benin